1994
DOI: 10.1099/0022-1317-75-12-3603
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a secreted form of measles virus haemagglutinin expressed from a vaccinia virus recombinant

Abstract: The measles virus (MV) haemagglutinin (HA) is a class 2 glycoprotein by means of which the virus particle attaches to the host cell receptor. We have previously expressed this glycoprotein as a vaccinia recombinant virus and have shown that the HA glycoprotein synthesized is indistinguishable from that coded by MV. In the present study, we report that in RK13 cells a soluble form (sHA) of the HA is secreted into the medium. We show by SDS-PAGE and sucrose density gradient centrifugation that the sHA is a dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Soluble glycoproteins have been described for a number of viruses (Morimoto et al, 1993;Malvoisin and Wild, 1994;Roberts et al, 1994), but little is known about the mechanisms and the biological significance of their release. Inhibitory effect on GP 1,2D shedding TAPI-I (50 mM) + 1,10-Phenanthroline (1 mM) a + EDTA (5 mM) À EGTA (5 mM) À Phosporamidon À b a-1-Antichymotrypsin (4 mM) À Captopril (10 mM) À BB2516 (500 nM) + GM 6001 (5 mM Premature termination of translation has been suggested to be responsible for release of the carboxy-terminally truncated G protein of VSV (type I transmembrane glycoprotein) (Grü nberg et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble glycoproteins have been described for a number of viruses (Morimoto et al, 1993;Malvoisin and Wild, 1994;Roberts et al, 1994), but little is known about the mechanisms and the biological significance of their release. Inhibitory effect on GP 1,2D shedding TAPI-I (50 mM) + 1,10-Phenanthroline (1 mM) a + EDTA (5 mM) À EGTA (5 mM) À Phosporamidon À b a-1-Antichymotrypsin (4 mM) À Captopril (10 mM) À BB2516 (500 nM) + GM 6001 (5 mM Premature termination of translation has been suggested to be responsible for release of the carboxy-terminally truncated G protein of VSV (type I transmembrane glycoprotein) (Grü nberg et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…By using monomer-and oligomer-specific antibodies to influenza virus hemagglutinin, it was shown that monomers are restricted to the ER, whereas assembled molecules are able to reach distal points in the transport pathway (9). Furthermore, a fraction of the hemagglutinin of measles virus expressed from a vaccinia virus recombinant was found to be released into the culture medium as a dimer (35). These are but a few examples emphasizing the importance of the oligomeric assembly in the efficient transport of viral glycoproteins, which may be regarded as a likely explanation for the retention of the PRRSV GP 3 in the ER.…”
Section: Discussionmentioning
confidence: 99%
“…Confluent MARC-145 cells growing in 150-cm 2 flasks (3 ϫ 10 7 cells) were infected with 10 7were infected with AdCMV5/ORF3 at an MOI of 20 to 30 TCID 50 /cell. At 24 h p.i., cells were pulse-labelled with [ 35 ]methionine for 30 min (time zero), chased for the indicated times, and processed for radioimmunoprecipitation with ␣3 antiserum. Aliquots of immunoprecipitates were treated with Endo H or Glyco F or were left untreated (UNT) and were then analyzed by SDS-12% PAGE.…”
Section: Processing Of Gp 3 Individually Expressed In 293 Cells By a mentioning
confidence: 99%
“…A useful approach to develop viral membrane glycoproteins suitable for panning phage libraries or as antigens for eliciting antibody responses that recognize their native form is to engineer soluble and secreted versions of the molecules. Often, this approach yields a quaternary structure similar to their native counterparts, and for animal viruses eukaryotic expression systems are typically employed such as recombinant bacculovirus or vaccinia virus, or transient or stable expression in cell culture (22,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). This chapter will detail several methods that have been successfully employed to produce, purify, and characterize soluble and secreted versions of several viral envelope glycoproteins which have been successfully used as antigens to capture and isolate human phage-displayed mAbs.…”
Section: Introductionmentioning
confidence: 99%